Analisis Spasial Kasus Persebaran Tuberkolosis Kabupaten dan Kota di Provinsi Jawa Barat Tahun 2022-2024 - Muhammad Najiy Yullah (Router : Jurnal Teknik Informatika dan Terapan, 2025)
Tuberculosis (TB) is one of the infectious diseases that remains a public health problem in Indonesia, including in West Java Province, which has a large population and high mobility. This condition has the potential to increase the risk of transmission and cause variations in the distribution of cases between districts and cities. This study aims to map the distribution of TB cases across all districts and cities in West Java Province from 2022 to 2024 using a spatial analysis approach. This analysis was conducted to describe the geographical distribution of cases, identify patterns of spread, and determine areas with relatively high or low case rates. TB data was obtained from routine recording and reporting by health facilities in West Java, then integrated with population and administrative boundary data. The results of the analysis provide information on case distribution patterns between regions and trends in case changes from year to year. The findings of this study are expected to serve as a basis for local governments in formulating more targeted TB prevention and control strategies, through a focus on interventions in areas with a high case burden, as well as optimizing sustainable public health programs in West Java Province.